Teaching Humanity Using Picture Books in Preschool Education - Nordin, Norazly; Senn, Joanne Lo Fui; Rashid, Muhammad Hilmi Abdul (Kiddie: Early Childhood Education and Care Journal, 2026)
Picture books play a vital role in early childhood education by fostering empathy, moral reasoning, and cultural awareness through engaging stories and illustrations. By exposing children to diverse characters, situations, and perspectives, picture books help young learners understand emotions, social relationships, and ethical values in developmentally appropriate ways. This study explores the effectiveness of picture books as a pedagogical tool for teaching humanity in preschool settings. Through a qualitative approach using focus group discussions (FGD), insights were gathered from six participants which are educators, storytellers, and publishers to explore the potential and the characteristics of picture books in teaching humanity to pre-schoolers. The findings highlight that picture books are potentially used in teaching humanity because able in fostering empathy; enhancing moral and ethical reasoning; make learning more interactive and engaging; and able to promote cultural awareness and Identity to children. The study also reveals six characteristic of picture books to be used in teaching humanity such as relatable and diverse character; engaging illustration; simple and clear language; moral and ethical lessons; interactive elements; and culturally sensitivity. The findings have significant implications for curriculum development, teacher training, and policy-making in early childhood education, particularly in multicultural contexts like Malaysia. This research contributes to the growing body of literature on the educational potential of picture books, offering practical insights for educators, policymakers, and parents.